1998
DOI: 10.1063/1.367572
|View full text |Cite
|
Sign up to set email alerts
|

The effect of boron and rare earth contents on the magnetic properties of La and Cr substituted α-Fe/R2Fe14B-type nanocomposites

Abstract: Influence of microstructure on magnetic properties of nanocomposite RE 5.5 ( Fe,Cr,M ) 76.5 B 18 (RE=Nd, Tb; Cr3 at%; M=Co,Si) magnetic materials

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
6
0

Year Published

2003
2003
2013
2013

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 11 publications
(10 reference statements)
1
6
0
Order By: Relevance
“…Similar results were obtained by Chen et al [20]. The metastable R 2 Fe 23 B 3 phase can be entirely prohibited by increasing the content of rare earth elements [21] or by decreasing the B concentration [22]. Based on the XRD results, one can conclude that Zr, Nb or Ti atoms occupy the Pr sites, act as Pr, and this comparatively increases the content of Pr in the alloy.…”
supporting
confidence: 87%
“…Similar results were obtained by Chen et al [20]. The metastable R 2 Fe 23 B 3 phase can be entirely prohibited by increasing the content of rare earth elements [21] or by decreasing the B concentration [22]. Based on the XRD results, one can conclude that Zr, Nb or Ti atoms occupy the Pr sites, act as Pr, and this comparatively increases the content of Pr in the alloy.…”
supporting
confidence: 87%
“…4 presents the composition dependence of the phase evolution in the initially as-spun ribbons (V s = 18 m/s). By comparing the relative peak heights for the magnetic phases in the TMA scans for different compositions, it was easily concluded that the content of metastable 2:17 phase in the ribbons is decreased with increasing Pr and Ti substitution [14].…”
Section: Resultsmentioning
confidence: 98%
“…In the present article, the phase evolution and magnetic properties of the Pr x Fe 82−x−y Ti y Co 10 B 4 C 4 (x = 9-10.5; y = 0, 2) ribbons with low rare-earth content have been systematically investigated. The effects of melt-spinning speed and annealing on the crystallization process, the resulting nanocrystalline phase structures, and the magnetic properties of the Pr 2 (Fe, Co) 14 (C, B)-type nanocomposites with different Pr and Ti contents, are reported and discussed.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Cr 2 B 10 ribbons with middle high boron content [5,6]. Similarly, B r , i H c and (BH) max values of 8.4-9.6 kG, 9.5-14.3 kOe and of 13.4-16.2 MGOe, respectively, have been obtained on the ternary Pr 9.5À11.76 Fe bal.…”
Section: Introductionmentioning
confidence: 96%